Future directions for Chinese accounting research - Qi Chen; Katherine Schipper (China Journal of Accounting Research, 2008)
Capital-markets based accounting research in China has a relatively short history; the two principal stock exchanges in Shanghai and Shenzhen have operated for less than 20 years. Recent accounting research has tended to adopt techniques, research designs and even topics that were developed in North America and apply them to the Chinese setting. This paper describes several aspects of the current empirical-archival focus of accounting research in China and offers some suggestions for expanding that focus to include analytical modeling and judgment-decision making experimentation. The paper also suggests there is a need to adjust existing research designs and methods for special features of the Chinese economy and its institutional arrangements. Finally, the paper puts forward some examples of research areas where Chinese accounting researchers can make useful contributions. In this discussion of possible research areas, we distinguish between the motivating question, which establishes the importance of the research inquiry, and the research question itself, which is relatively narrow and specifically focused on one aspect of the motivating question.
Keywords: 650